Implementation of the ROP (Reorder Point) Algorithm on the Parts Stock Management Information System at PT Indako Trading Coy Web based - Dalimunthe, Isma Nurlita; Suendri, Suendri (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
PT. Indako Trading Coy is a dialer that operates in the field of selling motorbikes. Data processing is a routine matter in a company. At PT. Indako Trading Coy data processing is still done manually, such as managing spare parts stock is still done by typing and printing data one by one and searching for this data takes a long time so it is necessary to implement an information system that supports goods data management. For this reason, a computerized system support is needed, which can help owners and employees in the process of managing spare parts stock for the progress of PT. Indako Trading Coy. This system is designed using a Reorder Point algorithm to ensure sufficient inventory that can be used to meet customer demand and helps companies avoid overflowing inventory in the warehouse. The system was designed using UML (Unified Modeling Language) design and using the PHP programming language with a MySQL database. This system design also uses the UCD (User Centered Design) system development method which discusses what is needed and needed by system users, therefore this application design can work optimally. It is hoped that this system can be used and is able to help PT. Indako Trading Coy in knowing the amount of spare parts stock needed to improve staff performance in working on spare parts stock management reports so that they become more effective and efficient.